Social technologies in public libraries: exploring best practice. Issue 3 (4th March 2014) - Smeaton, Kathleen; Davis, Kate
Abstract : Purpose: – The purpose of this article is to report on a research project that explored social media best practice in the public library sector. Design/methodology/approach: – The primary research approach for the project was case study. Two organisations participated in case studies that involved interviews, document analysis, and social media observation. Findings: – The two case study organisations use social media effectively to facilitate participatory networks, however, there have been challenges surrounding its implementation in both organisations. Challenges include negotiating requirements of governing bodies and broader organisational environments, and managing staff reluctance around the implementations. As social media use continues to grow and libraries continue to take up new platforms, social media must be considered to be another service point of the virtual branch, and indeed, for the library service as a whole. This acceptance of social media as being core business is critical to the successful implementation of social media based activities. Practical implications: – The article provides an empirically grounded discussion of best practice and the conditions that support it. The findings are relevant for information organisations across all sectors and could inform the development of policy and practice in other organisations. This paper contributes to the broader dialogue around best practice in participatory service delivery and social media use in library and information organisations. Originality/value: – Research around social media has focused on the usage of tools rather than the conditions that allow staff to use social media to reach users effectively. This research fills the gap by exploring the organisational culture that allows staff to use social media in order to develop a participatory library service.